ANALISIS GAYA BAHASA SINDIRAN DALAM ALBUM S’NADA TRIO VOLUME 3 KARYA YUNUS GEA - Pianus Zai; Bimerdin Daely; Askarman Laia (Universitas Nias Raya, 2022)
This research is motivated by the uniqueness of using language styles, especially in satire language style with nuanced criticism in the form of satire against certain people so as to create a state or feeling of the heart, whether it is a pleasant impression or a bad impression. One of them is the satire language style contained in the album, the satire language style is a language style that uses sentences or words that are meant to be satirical. The purpose of this study is to describe the types of satire language styles contained in the Album S'nada Trio Volume 3 by Yunus Gea; describe the satire language style contained in the album S'nada Trio Volume 3 by Yunus Gea irony, cynicism, sarcasm, antifrasis. This study uses a qualitative approach with a descriptive method. Based on the results of research in Yunus Gea's S'nada Trio album Volume 3 that there is a satire language style, namely the satire language style in the album S'nada Trio Volume 3 by Yunus Gea, namely irony there is 1 quote, cynicism is 1 quote, sarcasm is 3 citations, antiphrases there are 2 quotes, and in all there are 7 quotes. In the album S'nada Trio Volume 3, Yunus Gea's work can be used as a guide or illustration for the community, and as learning at school, one of which is for students. This can be applied in Indonesian subjects, especially material on literature. Suggestions, to teachers and prospective teachers of Indonesian Language and Literature, Indonesian language subject teachers should make the album S'nada Trio Volume 3 by Yunus Gea as a source of student learning in literary learning, the authors of the S'nada Trio album should use more language styles so that the lyrics of the song are more interesting, further researchers should use this research as a reference material to conduct relevant research.